2022
DOI: 10.3390/catal12030263
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of pH, Metal Ions, and Insoluble Solids on the Production of Fumarate and Malate by Rhizopus delemar in the Presence of CaCO3

Abstract: Calcium carbonate has been extensively used as a neutralising agent in acid-forming microbial processes. The effect of increasing calcium carbonate concentrations on Rhizopus delemar has not been previously investigated. In this study, an evaluation of fumaric acid (FA) and malic acid (MA) production was conducted at three CaCO3 concentrations in shake flask cultivations. Increased CaCO3 concentrations resulted in the co-production of FA and MA in the first 55 h of the fermentation (regime 1), and the subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Although the final FA concentration for fermentation with free and immobilized cells was slightly different (31.23 and 32.03 g/L, respectively), the volumetric productivity for fermentation with immobilized cells (1.335 g/L/h) was six times higher than that for fermentation with free cells (0.217 g/L/h). Ronoh et al (2022) reported the effect of CaCO3 on the co-production of FA and malic acid by the immobilized R. delemar . The increased concentration of calcium ions to 10 g/L resulted in a three-fold enhancement of MA titres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the final FA concentration for fermentation with free and immobilized cells was slightly different (31.23 and 32.03 g/L, respectively), the volumetric productivity for fermentation with immobilized cells (1.335 g/L/h) was six times higher than that for fermentation with free cells (0.217 g/L/h). Ronoh et al (2022) reported the effect of CaCO3 on the co-production of FA and malic acid by the immobilized R. delemar . The increased concentration of calcium ions to 10 g/L resulted in a three-fold enhancement of MA titres.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, fungal cell immobilization for fermentation is complex process influenced by various parameters. One crucial parameter is fungal morphology, which is directly affected by culture conditions, including agitation rate, temperature, medium composition, initial spore concentration, and the immobilization matrix used ( Ronoh et al, 2022 ). Our study demonstrated that, despite the potential use of immobilized cells for FA fermentation, they proved to be less efficient and productive compared to free cells.…”
Section: Discussionmentioning
confidence: 99%
“…With 60 or 100 g/L CaCO 3 compared to 20 g/L, carbonate was available until the end of the fermentation, which prevented a drop in pH and resulted in a higher malic to fumaric acid ratio. The authors ruled out the presence of insoluble solids as influencing factor but found increased ion concentrations and different pH values to affect the production profile [ 39 ]. Schmitt et al also observed a positive effect of calcium carbonate on malic acid productivity and associated it with its ability to control the pH as buffering agent, although the authors pointed out that this may not be its only function [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ronoh et al reported a decreased glucose consumption and fumaric acid production of R. delemar with 20 g/L Ca 2+ in the medium, which suggests inhibition. However, they also observed an increased, albeit delayed, formation of malic acid which might be attributed to a stimulatory effect of Ca 2+ on the enzyme fumarase [ 39 ]. The results described in all these references were obtained for cultivations using glucose as carbon source.…”
Section: Discussionmentioning
confidence: 99%
“…in which it was further proposed that many of the effects and interactions of Ca 2+ with fungal physiology link to the maintenance of Ca 2+ homeostasis, with multiple channels and transporters dedicated to this task. Consequently, the magnitude of these effects is likely to be complex with synchronous interactions likely -as was observed in a recent study by Ronoh et al 44 in which a compounded interaction between Ca 2+ and pH were observed to affect the production of MA by Rhizopus oryzae.…”
mentioning
confidence: 93%